Microbial Symbiont-Based Detoxification of Different Phytotoxins and Synthetic Toxic Chemicals in Insect Pests and Pollinators - Olivia Kline; Neelendra K. Joshi (MDPI AG, 2024)
Insects are the most diverse form of life, and as such, they interact closely with humans, impacting our health, economy, and agriculture. Beneficial insect species contribute to pollination, biological control of pests, decomposition, and nutrient cycling. Pest species can cause damage to agricultural crops and vector diseases to humans and livestock. Insects are often exposed to toxic xenobiotics in the environment, both naturally occurring toxins like plant secondary metabolites and synthetic chemicals like herbicides, fungicides, and insecticides. Because of this, insects have evolved several mechanisms of resistance to toxic xenobiotics, including sequestration, behavioral avoidance, and enzymatic degradation, and in many cases had developed symbiotic relationships with microbes that can aid in this detoxification. As research progresses, the important roles of these microbes in insect health and function have become more apparent. Bacterial symbionts that degrade plant phytotoxins allow host insects to feed on otherwise chemically defended plants. They can also confer pesticide resistance to their hosts, especially in frequently treated agricultural fields. It is important to study these interactions between insects and the toxic chemicals they are exposed to in order to further the understanding of pest insect resistance and to mitigate the negative effect of pesticides on nontarget insect species like Hymenopteran pollinators.